The Effectiveness of Web-Based PACTA for Electrical Motor Installation in Vocational High School - Mustaqim, Bima; Siagian, Sahat; Junaidi, Agus; Keristiana Sinaga, Enny; Tanjung, Samsidar; Mursid, R (Universitas Pendidikan Ganesha, 2025)
Vocational education in Indonesia faces challenges in providing interactive learning that aligns with the demands of Industry 4.0. In addition, students’ low engagement in understanding technical concepts remains a major obstacle to achieving meaningful learning outcomes. This study aims to evaluate the effectiveness of a web-based learning system using the PACTA model in improving student learning outcomes. The research employed a quasi-experimental method with a pre-test and post-test design across two groups: one group used the PACTA system integrated with Augmented Reality (AR) and an AI-based chatbot, while the other group used a conventional web-based learning platform. Results showed that the PACTA group experienced an increase in average score from 45.22 to 63.91 (t = 3.508; p = 0.002) with an effect size of 18.69%, while the conventional group improved from 38.04 to 44.79 (t = 2.273; p = 0.031) with an effect size of 6.75%. Student perception data showed high satisfaction, with effectiveness at 90.67%, ease of use at 88.2%, and accessibility at 85.0%. The findings conclude that the PACTA-based learning system effectively enhances student engagement and understanding and is recommended for broader application in vocational education.